Efficacy of school-based intervention programs in reducing overweight: A randomized trial - Marsigliante, Santo; Ciardo, Vito; Di Maglie, Antonio; My, Giulia; Muscella, Antonella (Frontiers in Nutrition, 2022)
Childhood obesity is increasingly being recognized as a major public health problem. The objective of the present study was to evaluate the effectiveness of a school-based education intervention on improving the knowledge and behavior of primary-school children towards better dietary habits. The strategy was implemented over a 6-month period. The participants students were randomly assigned to the intervention (n= 200) and non-intervention groups (n= 197). Participants had mean body mass index of 18.3 ± 2.7 kg/m2, and its change in intervention group (−2.7 ± 0.5 kg/m2) was significantly different from that in control group (3.41 ± 0.8 kg/m2). On the other hand, there are significant differences between proportion of overweight, underweight, normal weight or with obesity children pre and post intervention, in experimental group (p< 0.05). The best results were observed in the female sex, since there were no girls with obesity, after the intervention. The effects on waist circumference were also significant in intervention group compared with control group (p<0.05). In addition, many of the participating children acquired healthy eating habits. The findings suggest that a school-based intervention program represents an effective strategy in prevention of childhood overweight and obesity problem and our results quantitatively supported this argument.